Lexical Cohesions in A Grade X English Textbook by Indonesian Education and Culture Ministry - Muhammad Zahrudhin Verdiansyah; Sahiruddin Sahiruddin; Putu Dian Danayanti Degeng (Unipdu Jombang, 2019)
The article aims to examine the patterns of lexical cohesion in light of the cohesion model proposed by Halliday and Hasan in 1976. Halliday and Hasan identified 2 categories of lexical cohesion which are: reiteration and collocation. Though, the present study merely discussed the category of reiteration. This study uses English textbook of Indonesian X Grade Senior High School Students published by Indonesian Education & Culture Ministry. Analysis of text comprises Halliday and Hasan’s cohesion model, and analyze linguistic techniques used in the textbook. The result of the study found repeated occurrences of lexical cohesion of reiteration which are: repetition, synonym or near-synonym & superordinate. The sub-category of synonym or near – synonym was found to be the most frequently occurring lexical cohesion; suggesting that the English textbook of Indonesian X Grade Senior High School Students published by Indonesian Education & Culture Ministry are cohesive.Keyword: English textbook, Lexical cohesion